The Role of Local Governments in Conserving Cultural Ornaments: A Case Study of Banten and Cirebon Mosques - SUKARWO, WIRAWAN; MUNTAZORI, AHMAD FAIZ; WULANDARI (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
Globalization is a phenomenon that cannot be avoided. The openness of information and communication today makes the intrusion of foreign cultures increasingly unavoidable. Local culture based on community and tradition is threatened to slowly disappear. On the other hand, the spirit of Muslims to worship is increasingly globally oriented. For example, the current trend of building mosques with Middle Eastern ornament designs in Indonesia. Conservation of local culture can be effectively achieved through the design of mosque ornaments that apply local cultural ornamental motifs. This research is a descriptive qualitative type with a case study approach. Data collection in this research uses observation and literature study methods. The objects that became case studies in this research were iconic mosques in Banten and Cirebon. The conclusion of this research is the crucial role of the local government in bridging local cultural conservation efforts with the spirit of religiosity of Muslims.